The Preparation of (Bi0.5Na0.5)0.94 (Ba0.945Ca0.055)0.06(Ti0.9946Sn0.0054)O3 :Y2.7Bi0.3Fe4.7Mn0.3O12 Composite Ceramics with Multiferroic Properties Via Solid-State Combustion Technique - Wichasilp, Chanade; Pinitsoontorn, Supree; Bongkarn , Theerachai; Kronphom, Chittakorn (Burapha Science Journal, 2024)
Background and Objectives : This research focuses on the preparation of ceramic composites with multiferroic properties of (Bi0.5Na0.5)0.94 (Ba0.945Ca0.055)0.06(Ti(0.9946) Sn0.0054)O3 (BNT-BCTS) with mixing Y2.7Bi0.3Fe4.7Mn0.3O12 (YBFM) at various ratios by solid-state combustion technique. The effect of ratios on phase structure, microstructure, electrical properties, and magnetic properties of the prepared ceramic composites were studied. Methodology : The ceramic composite of (Bi0.5Na0.5)0.94 (Ba0.945Ca0.055)0.06(Ti(0.9946) Sn0.0054)O3 (BNT-BCTS) with mixing Y2.7Bi0.3Fe4.7Mn0.3O12 (YBFM) compound at various ratios of 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, and 3:7 wt% was prepared by solid-state combustion with glycine as fuel. Main Results : It was found that the ratio of all ceramics showed perovskite structure with coexisted phases of rhombohedral and tetragonal phases mixed a garnet structure. The intensity of the garnet structure increased with increasing of the YBFM ratios. Grain ceramics showed mixture of large grains and small grains in all ceramics and grains exhibited polygonal shapes. Average grain size density of the ceramics deceased while the density of the ceramics increased from 5.75 g.cm-3 to 5.96 g.cm-3 when the YBFM ratios increased. In the analysis of dielectric property at room temperature with measuring at 1 kHz of the ceramics at various ratios, it was observed that the dielectric constant ( r) decreased. In contrast, the dielectric loss (tan r) increased when the YBFM ratios increased. The analysis of ferroelectric properties from P-E loops at room temperature of all ceramics, it was found that all P-E loops showed non-saturated loops and the P-E loos showed bloated loops with increasing the YBFM ratios which indicated that leakage current was formed. The Ps value of the ceramics was in the range of 1.72 - 5.97 µC/cm2. When the YBFM ratios increased, the Pr and Ec values were increased. For magnetic property of all ceramic ratios with measuring at 27oC, showed that all ceramics showed the ferromagnetic property. The value of saturated magnetic (Ms), Remnant magnetic (Mr), and Magnetic coercive field (Hc) of all ceramic ratios were in the range of 0.12-5.01 emu/g, 0.003-2.28 emu/g and 61.25-149.19 Oe, respectively, all values increased with increasing the YBFM ratios. Conclusions : The BNT-BCTS:YBFM ceramic composite exhibited ferroelectric and ferromagnetic coupling properties, which were important characteristics of multiferroic materials. However, at volume ratios of 5:5 to 3:7, the ceramic has a large leakage current, which was a range of inappropriate ratios. Moreover, it is not possible to confirm that the ratio of ceramic was the best. Therefore, further study of the magnetoelectric coefficient is required in the future.